Heparan sulfate deficiency in cartilage: enhanced BMP-sensitivity, proteoglycan production and an anti-apoptotic expression signature after loading - Gerstner, Matthias; Severmann, Ann-Christine; Chasan, Safak; Vortkamp, Andrea; Richter, Wiltrud (International journal of molecular sciences, 2021)
Osteoarthritis (OA) represents one major cause of disability worldwide still evading efficient pharmacological or cellular therapies. Severe degeneration of extracellular cartilage matrix precedes the loss of mobility and disabling pain perception in affected joints. Recent studies showed that a reduced heparan sulfate (HS) content protects cartilage from degradation in OA-animal models of joint destabilization but the underlying mechanisms remained unclear. We aimed to clarify whether low HS-content alters the mechano-response of chondrocytes and to uncover pathways relevant for HS-related chondro-protection in response to loading. Tissue-engineered cartilage with HS-deficiency was generated from rib chondrocytes of mice carrying a hypomorphic allele of Exostosin 1 (Ext1), one of the main HS-synthesizing enzymes, and wildtype (WT) littermate controls. Engineered cartilage matured for 2 weeks was exposed to cyclic unconfined compression in a bioreactor. The molecular loading response was determined by transcriptome profiling, bioinformatic data processing, and qPCR. HS-deficient chondrocytes expressed 3-6% of WT Ext1-mRNA levels. Both groups similarly raised Sox9, Col2a1 and Acan levels during maturation. However, HS-deficient chondrocytes synthesized and deposited 50% more GAG/DNA. TGFβ and FGF2-sensitivity of Ext1gt/gt chondrocytes was similar to WT cells but their response to BMP-stimulation was enhanced. Loading induced similar activation of mechano-sensitive ERK and P38-signaling in WT and HS-reduced chondrocytes. Transcriptome analysis reflected regulation of cell migration as major load-induced biological process with similar stimulation of common (Fosl1, Itgα5, Timp1, and Ngf) as well as novel mechano-regulated genes (Inhba and Dhrs9). Remarkably, only Ext1-hypomorphic cartilage responded to loading by an expression signature of negative regulation of apoptosis with pro-apoptotic Bnip3 being selectively down-regulated. HS-deficiency enhanced BMP-sensitivity, GAG-production and fostered an anti-apoptotic expression signature after loading, all of which may protect cartilage from load-induced erosion.